Understanding Barriers and Facilitators of Parent/Caregiver Involvement in Home-Based Applied Behavioral Analysis Programming for Their Autistic Child - Lisa A. Ferretti; Astrid Uhl; Jessica Zawacki; Philip McCallion (Children, 2025)
There is a need for more attention to the importance of substantial parent involvement in programming for autistic children in community-based care. More encouragement is needed to ensure that practitioners prioritize parental training and involvement throughout interventions, including practitioner-led in-home applied behavioral analysis (ABA) interventions. There has been little to no research on the feasibility and efficacy of adding parental training to in-home practitioner-led ABA interventions. This study is intended to begin the consideration of efficacy by reporting on a series of focus groups involving parents of autistic children and the Board Certified Behavioral Analysts (BCBAs) and Registered Behavior Technicians (RBTs) who work with them. Method: Focus group meetings were conducted with a total of 18 participants: 7 family members, 5 RBTs, and 6 BCBAs drawn from two provider sites. Transcripts were generated, and data was analyzed using Braun & Clarke’s reflexive thematic analysis, a method for analyzing and interpreting qualitative data that involves systematically generating codes in order to develop themes. Findings: The findings are described using three main themes: (1) barriers to family involvement in applied behavioral analysis programming, (2) facilitators of family involvement in applied behavioral analysis programming, and (3) recommendations for improving family involvement in applied behavioral analysis programming. Conclusions: There are logistical challenges in involving parents in in-home interventions when they occur in evening hours when the family has multiple other responsibilities. However, being in-home also presents opportunities not available in school or clinic settings. The recommendations provided offer an initial road map to advancing parent training components.